Evaluation of an explicit NOx chemistry method in AERMOD. (3rd June 2017) - Carruthers, David J.; Stocker, Jenny R.; Ellis, Andrew; Seaton, Martin D.; Smith, Stephen E.
ABSTRACT: An explicit NOx chemistry method has been implemented in AERMOD version 15181, ADMSM. The scheme has been evaluated by comparison with the methodologies currently recommended by the U.S. EPA for Tier 3 NO2 calculations, that is, OLM and PVMRM2. Four data sets have been used for NO2 chemistry method evaluation. Overall, ADMSM-modeled NO2 concentrations show the most consistency with the AERMOD calculations of NOx and the highest Index of Agreement; they are also on average lower than those of both OLM and PVMRM2. OLM shows little consistency with modeled NOx concentrations and markedly overpredicts NO2 . PVMRM2 shows performance closer to that of ADMSM than OLM; however, its behavior is inconsistent with modeled NOx in some cases and it has less good statistics for NO2 . The trend in model performance can be explained by examining the features particular to each chemistry method: OLM can be considered as a screening model as it calculates the upper bound of conversion from NO to NO2 possible with the background O3 concentration; PVMRM2 includes a much-improved estimate of in-plume O3 but is otherwise similar to OLM, assuming instantaneous reaction of NO with O3 ; and ADMSM allows for the rate of this reaction and also the photolysis of NO2 . Evaluation with additional data sets is needed to further clarify the relative performance of ADMSM and PVMRM2. Implications : Extensive evaluation of the current AERMOD Tier 3 chemistry methods OLM and PVMRM2, alongside a new scheme that explicitly calculates the oxidation of NO by O3 and the reverse photolytic reaction, shows that OLM consistently overpredicts NO2 concentrations. PVMRM2 performs well in general, but there are some cases where this method overpredicts NO2 . The new explicit NOx chemistry scheme, ADMSM, predicts NO2 concentrations that are more consistent with both the modeled NOx concentrations and the observations.